Doppler ultrasonography in lower extremity peripheral arterial disease - Samet Verim; İlker Taşçı (KARE Publishing, 2013)
Systemic atherosclerosis is a condition which progresses with age, decreases quality of life, and life expectancy. Lower extremity peripheral arterial disease (PAD) is a common manifestation of systemic atherosclerosis in the elderly. These individuals have a 2 to 4 fold higher risk of coronary heart disease and stroke. In addition, systemic atherosclerosis causes overall functional disability including restricted lower extremity movements. When used alone for diagnostic purposes, claudication is an unreliable sign of PAD in all age groups especially the elderly. Moreover, claudication is difficult to define due to the advancing age and degenerative changes in lumbar and peripheral joints. Doppler ultrasonography (US) is an easily available and noninvasive means of arterial visualization in the lower extremities. In this review, supporting evidence for the use of Doppler US in the diagnosis of PAD will be discussed. Past and present recommendations regarding Doppler US in the current PAD guidelines will be overviewed.